Analisis Impact Aktivitas Shalat berjamaah terhadap TingkahLakuPesertaDidik (Studi di SMA Negeri 1 WundulakoKab. Kolaka Sulawesi Tenggara) - Nur Hayati (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Carrying out congregational prayers can train discipline, mutual respect, respect without any differences, and these good habits can be implemented into everyday life. Activity is an activity that is carried out sincerely and sincerely which leads to a positive collar. Activities can be defined as various activities that direct all energy, thought, and physical to achieve a goal. Prayers in congregation are prayers that are performed together, which are performed by at least two people. Behavior is a person's attitude which is manifested in actions. The method used is quantitative descriptive method. Based on the presentation and data analysis, it can be concluded that the congregational prayer activity has an impact on the behavior of students at SMA Negeri 1 Wundulako.